1984
DOI: 10.1182/blood.v63.1.162.162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transfusion therapy on arteriographic abnormalities and on recurrence of stroke in sickle cell disease

Abstract: Stroke is a relatively frequent and severe complication of sickle cell disease. We performed cerebral arteriograms in 30 patients with sickle cell disease to evaluate the cause of acute neurologic deficits and to assess the effects of transfusion therapy given for a year or more after the acute episode. Twenty-three patients with motor and speech deficits had multiple abnormalities of major cerebral arteries. The internal carotid and anterior and middle cerebral arteries showed stenosis and/or occlusion at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(70 citation statements)
references
References 0 publications
1
68
0
1
Order By: Relevance
“…Without intervention, children with sickle cell anemia (SCA) are over 300 times more likely to suffer a stroke than children without SCA, and 11% of children with SCA will have overt stroke by the age of 20 years [1]. These young patients often have significant disability, poor neurocognitive outcomes and a high risk of stroke recurrence (47–93%) [2–4]. Chronic transfusion therapy reduces but does not eliminate the risk of recurrent stroke, with published rates ranging from 10% to 23% or 2.2 to 4.8 events per 100 patient‐years, [2, 5, 6] and the risk of recurrent stroke increases further once transfusions are stopped [7–9].…”
Section: Introductionmentioning
confidence: 99%
“…Without intervention, children with sickle cell anemia (SCA) are over 300 times more likely to suffer a stroke than children without SCA, and 11% of children with SCA will have overt stroke by the age of 20 years [1]. These young patients often have significant disability, poor neurocognitive outcomes and a high risk of stroke recurrence (47–93%) [2–4]. Chronic transfusion therapy reduces but does not eliminate the risk of recurrent stroke, with published rates ranging from 10% to 23% or 2.2 to 4.8 events per 100 patient‐years, [2, 5, 6] and the risk of recurrent stroke increases further once transfusions are stopped [7–9].…”
Section: Introductionmentioning
confidence: 99%
“…Another excellent example of gathering definitive evidence to support benefit from TA can be found in the use of maintenance RBC exchange (RBCX) to prevent ischemic stroke in children with sickle cell disease. Building on observational data suggesting that transfusion to maintain a patient's hemoglobin S level less than 30% after a first stroke lowered the risk of a second stroke, 38,39 a network of centers carried out a pair of randomized controlled trials. The first showed conclusively that the same transfusion strategy lowers the risk of a first stroke in children with central nervous system (CNS) vascular abnormalities detected by transcranial Doppler ultrasound 40 .…”
Section: Clinical Application Of Tamentioning
confidence: 99%
“…There are no studies, to date, specifically investigating the impact of different percent HbA or HbS goals in chronic transfusion therapy for stroke prevention or for any complication of SCD. The clinical trial designs requiring pre‐transfusion HbS to be less than 30% were based on early literature investigating secondary stroke prevention with transfusion therapy . Of note, all subjects included in these early cohort studies had a history of overt stroke, and many of the participants had vasculopathy confirmed with arteriogram.…”
mentioning
confidence: 99%